2020
DOI: 10.34067/kid.0000402019
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload and Mortality in Patients with Severe Acute Kidney Injury and Extracorporeal Membrane Oxygenation

Abstract: Background: Volume overload is increasingly being understood as an independent risk factor for increased mortality in the setting of acute kidney injury (AKI) and critical illness, but little is known about its impact in the setting of extracorporeal membrane oxygenation (ECMO). We sought to evaluate the incidence of AKI and volume overload and their impact on all-cause mortality in adults following ECMO cannulation. Methods: We identified all adult patients who underwent ECMO cannulation at the University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In cases of significant FO, acute pulmonary edema refractory to diuretics with PaO2/FiO2 < 300 mmHg, a resource in this clinical scenario, is Slow Continuous Ultrafiltration (SCUF) and/or CKRT depending on the clinical requirement, and these are alternatives that have been extensively studied with conflicting results. In a retrospective cohort study of 98 critically ill patients who required ECMO, 85% of them developed AKI, and of these, 49% required CKRT; in those who had FO > 10% 72 hours after connection to ECMO and developed severe AKI, 90-day mortality was higher when compared to those who did not develop AKI (HR 2.2; 95% CI, 1.3 to 3.8; p = 0.004) and those in the subgroup requiring CKRT had higher mortality (p = 0.029), and it is observed that CKRT does not ensure a negative fluid balance, but helps to achieve a less positive balance [97].…”
Section: Fluid Overloadmentioning
confidence: 98%
“…In cases of significant FO, acute pulmonary edema refractory to diuretics with PaO2/FiO2 < 300 mmHg, a resource in this clinical scenario, is Slow Continuous Ultrafiltration (SCUF) and/or CKRT depending on the clinical requirement, and these are alternatives that have been extensively studied with conflicting results. In a retrospective cohort study of 98 critically ill patients who required ECMO, 85% of them developed AKI, and of these, 49% required CKRT; in those who had FO > 10% 72 hours after connection to ECMO and developed severe AKI, 90-day mortality was higher when compared to those who did not develop AKI (HR 2.2; 95% CI, 1.3 to 3.8; p = 0.004) and those in the subgroup requiring CKRT had higher mortality (p = 0.029), and it is observed that CKRT does not ensure a negative fluid balance, but helps to achieve a less positive balance [97].…”
Section: Fluid Overloadmentioning
confidence: 98%
“…The authors evaluated the association between the timing of PP during ECMO and the prognosis and respiratory mechanics using various covariates. However, fluid balance (4) and the use of neuromuscular blockade during PP were not included as potential confounders. Because these covariates may have affected survival and respiratory mechanics, their effect needs to be assessed.…”
Section: To the Editormentioning
confidence: 99%